Exploring Cost Awareness and Budget Discipline in Housekeeping Operations: Evidence from a Four-Star Hotel in Jakarta - Ria Aryani; Yuni Deviyanti (Jurnal Sains Terapan Pariwisata, 2026)
This study examines how cost awareness and budget discipline are constructed and implemented within housekeeping operations in a four-star hotel in Jakarta. While budgeting systems and cost control procedures are formally established in most hospitality organizations, limited research has explored how these mechanisms are internalized at the operational level. Using a qualitative case study approach, data were collected through in-depth interviews with housekeeping managers, supervisors, room attendants, and accounting staff, complemented by document analysis and limited observation. Thematic analysis was employed to identify recurring patterns related to cost-related behavior and interdepartmental coordination. The findings reveal that cost awareness among housekeeping personnel primarily develops through operational experience and managerial communication rather than structured financial training. Budget discipline is maintained through formal approval procedures and hierarchical supervision; however, monitoring practices tend to be reactive rather than proactive. Interdepartmental collaboration between housekeeping and accounting departments plays a crucial role in reinforcing cost control, although tensions occasionally arise between financial efficiency and service quality objectives. Organizational culture and leadership communication significantly influence the translation of cost awareness into disciplined budgeting behavior, while operational pressures during high occupancy periods may weaken strict adherence to budget limits. The study contributes to hospitality managerial accounting literature by highlighting the behavioral and organizational dimensions of cost control in housekeeping operations. It proposes a contextual model in which cost awareness serves as a cognitive foundation for budget discipline, moderated by organizational culture and interdepartmental collaboration.